1992
DOI: 10.1002/bip.360320607
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a helical oligopeptide model of polyglycine II and of other polyamides: Acetyl‐(glycyl‐β‐alanyl)2NH propyl

Abstract: We synthesized and solved the crystalline structure of the oligopeptide acetyl-(glycyl-beta-alanyl)2-NH propyl. The crystal is formed by layers of helical molecules with the same chirality; however, right-handed layers alternate with left-handed ones. Inside every layer, the packing of helices is pseudohexagonal with hydrogen bonds between neighbor molecules. The structure found affords direct support for the model proposed by Crick and Rich for polyglycine II and also provides an interpretation for the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Figure 2 illustrates that the extended β‐Ala moiety continues into an infinite array of intermolecular interactions encompassing 14‐membered pseudo‐ring motif. It should be emphasized that, in marked contrast to parallel and antiparallel β‐sheet structures comprised of conventional α‐amino acids, the overall H‐bond geometric parameters of the observed ring motifs are unlikely to be influenced by parallel and/or antiparallel orientations of the interacting extended β‐Ala conformations because in each case the parallel dispositions of both the amide dipoles are essentially preserved (8–14). No additional C‐H…O‐type intermolecular interactions are favored (10,13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 illustrates that the extended β‐Ala moiety continues into an infinite array of intermolecular interactions encompassing 14‐membered pseudo‐ring motif. It should be emphasized that, in marked contrast to parallel and antiparallel β‐sheet structures comprised of conventional α‐amino acids, the overall H‐bond geometric parameters of the observed ring motifs are unlikely to be influenced by parallel and/or antiparallel orientations of the interacting extended β‐Ala conformations because in each case the parallel dispositions of both the amide dipoles are essentially preserved (8–14). No additional C‐H…O‐type intermolecular interactions are favored (10,13).…”
Section: Resultsmentioning
confidence: 99%
“…both residues restrict the backbone torsion angles in the 3 10 /α‐helical regions (φ ≈ ± 60 ± 20° and ψ ≈ ± 30 ± 20°) of the Ramachandran map (24,25). Furthermore, X‐ray crystallographic analysis of Boc‐β‐Ala‐Xaa‐NHCH 3 (where Xaa = l ‐Ala or d ‐Ala) and Ac‐(Gly‐β‐Ala) 2 ‐NHCH 2 CH 2 CH 3 , established that ‘significantly less constrained’ chiral, as well as achiral, residues are also capable of inducing diverse conformational characteristics across the β‐Ala residue (6,9,11). The results, including those reported by other investigators, inclined us to suggest that, in addition to stereochemical characteristics, the distinctive chemical nature of hydrophobic moieties of the neighboring residue may have pronounced influence on the conformational adaptability of the β‐Ala residue.…”
mentioning
confidence: 99%
“…Formation of a network of intermolecular hydrogen bonds can be justified by: (a) Conformational preferences of peculiar residues such as glycine and malonic acid and (b) Optimization of the hydrogen bonding geometry. Specifically, alternate copolymers and oligomers constituted by ω‐amino acid and glycine units adopt a similar structure (i.e., with three planar hydrogen bonding directions) to that described for polyglycine II, whereas structures with two hydrogen bonding directions have been postulated for polyamides derived from a diamine and malonic acid. This kind of structure was also deduced from crystallographic analysis of small model compounds …”
Section: Introductionmentioning
confidence: 93%
“…Rapidly growing interest in the conformational investigations of short linear peptides incorporating a β‐Ala residue has confirmed that, despite its inherent flexibility, the residue is capable of accommodating well‐defined structural mimetics of the β‐ and γ‐turns, helical and extended conformations (1–6). However, it also seems apparent that a number of stereochemical features can influence the stabilization of crystal molecular conformations of the noncoding β‐Ala moiety in short linear peptides (7–11).…”
mentioning
confidence: 99%